2011
DOI: 10.1021/ol200714h
|View full text |Cite
|
Sign up to set email alerts
|

1,2,3-Triazole Bound Au(I) (TA-Au) as Chemoselective Catalysts in Promoting Asymmetric Synthesis of Substituted Allenes

Abstract: The triazole-Au (TA-Au) complexes were identified as effective chemoselective catalysts in promoting propargyl ester/ether 3,3-rearrangements. The highly reactive allenes, which could not be isolated by simple cationic gold catalysts, were prepared in excellent yields (1% catalyst loading, >90% yields). Unlike other reported Au catalysts, the TA-Au provided effective chirality transfer without racemization over a long period of time, giving enantioenriched allenes with excellent stereoselectivity (1% catalyst … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 82 publications
(31 citation statements)
references
References 52 publications
1
30
0
Order By: Relevance
“…This finding must be seen in the context of previous literature reports which showed that gold-catalyzed [3,3]-sigmatropic rearrangements of propargylic esters are reversible and the resulting allenyl derivates subject to rapid racemization. [37,38] If this were true for 33 and 7-epi-33,t he configuration of the acetate-carrying C7 center should not matter.I tr emains to be seen whether the conflicting observations described herein are rooted in the peculiarities of the chosen catalyst or in the constraints of the particular substrate.Atthe meta level, however,this example bears witness to the notion that target-oriented synthesis often dissects scope and limitations of agiven transformation more rigorously than collections of model compounds and hence remains an eminent driver for method development.…”
Section: Communicationsmentioning
confidence: 99%
“…This finding must be seen in the context of previous literature reports which showed that gold-catalyzed [3,3]-sigmatropic rearrangements of propargylic esters are reversible and the resulting allenyl derivates subject to rapid racemization. [37,38] If this were true for 33 and 7-epi-33,t he configuration of the acetate-carrying C7 center should not matter.I tr emains to be seen whether the conflicting observations described herein are rooted in the peculiarities of the chosen catalyst or in the constraints of the particular substrate.Atthe meta level, however,this example bears witness to the notion that target-oriented synthesis often dissects scope and limitations of agiven transformation more rigorously than collections of model compounds and hence remains an eminent driver for method development.…”
Section: Communicationsmentioning
confidence: 99%
“…[13] This feature explains the observed reduced reactivity of TA-Auc ompared to the corresponding [L-Au] + catalyst. [14] In fact, monitoring TA-Au-catalyzed reactions by 31 PNMR spectroscopy showed TA-Auasthe dominant signal throughout the reaction (resting state). Using React IR and NMR spectroscopy,w er ecently reported the mechanistic studies of aT A-Au-catalyzed propargyl ester rearrangement.…”
mentioning
confidence: 99%
“…This finding must be seen in the context of previous literature reports which showed that gold-catalyzed [3,3]-sigmatropic rearrangements of propargylic esters are reversible and the resulting allenyl derivates subject to rapid racemization. [37,38] If this were true for 33 and 7-epi-33,t he configuration of the acetate-carrying C7 center should not matter.I tr emains to be seen whether the conflicting observations described herein are rooted in the peculiarities of the chosen catalyst or in the constraints of the particular substrate.Atthe meta level, however,this example bears witness to the notion that target-oriented synthesis often dissects scope and limitations of agiven transformation more rigorously than collections of model compounds and hence remains an eminent driver for method development.…”
Section: Methodsmentioning
confidence: 99%